Fitness Testing to Determine Pointe Readiness in Ballet Dancers. Issue 4 (December 2016) - Hewitt, Shayla; Mangum, Michael; Tyo, Brian; Nicks, Clayton
Pointe work requires substantial physical ability and effort. However, no standard measures exist to determine when a dancer is ready to begin to dance en pointe. This study explored whether physical tests could discriminate between pre-pointe, beginner pointe, and intermediate pointe students. The secondary purpose was to determine if teacher ratings of dancer performance and experience aligned with test scores. Twenty-nine female ballet students from two dance studios participated in the study (age: 13 ± 3 years; height: 155.7 ± 13.7 cm; weight: 50 ± 14.6 kg). They were divided into three skill groups: pre-pointe (N = 12), beginner pointe (N = 7), and intermediate pointe (N = 10). The participants completed five tests (heel rise, plank, sauté, topple, and airplane) used to measure physical attributes important to pointe training. In addition, the students' teachers rated each participant based on her ability to successfully complete all pointe work given for her level or, if she was a pre-pointe student, according to whether she was physically progressing at the appropriate rate to begin pointe. The findings of this study indicate that three tests (airplane, topple, and sauté) have some value in discriminating between dancers of different skill levels and may be useful for determining pointe readiness.